Aktualisasi Hukum Perceraian Perspektif Pengadilan Agama di Indonesia - Agus Toni (MAQASHID, 2018)
Islamic law must be understood more broadly in the context of statehood and nationality with all the differences in cultural, sociological and geographical types. This is a form of actualizing the values of Islamic teachings so that they can be accepted by humans as a whole. Maintain the sustainability of Islam itself and take greater benefit. As in Indonesia, with a different context from the east in various aspects such as geography, culture and social psychology of society, demanding that Islamic law be taught must have an elasticity value by leaving a form of inductive and conservative thinking structure. With a historical and philosophical understanding of Islamic law, it will bring progressive changes to the accommodative Islamic law by lokal people without going through opposition and rejection. Therefore, Indonesia has codified Indonesian-style Islamic law in the form of the Compilation of Islamic Law (KHI) and Law No. 1 of 1974, which are also used by the Religious Courts to decide cases including divorce. Especially if there is a movement to conduct an extension to the community and socialization of Islamic law products that are updated in Indonesia, it will certainly reduce the level of misunderstanding of the community towards divorce status. So that the classical Islamic law products that have been rooted at the level of society about when divorce is legitimate until in what context the divorce is rationally accepted and what constitutes strong constitutional evidence of divorce has been fulfilled by the rules of the Compilation of Islamic Law (KHI). Keywords: divorce, law, Islam, Indonesia